Skin Complications Associated With Pediatric Central Venous Access Devices: Prevalence, Incidence, and Risk. (September 2019) - Ullman, Amanda J.; Kleidon, Tricia M.; Turner, Karen; Gibson, Victoria; Dean, Anna; Cattanach, Paula; Pitt, Colleen; Woosley, Julieta; Marsh, Nicole; Gavin, Nicole; Takashima, Mari; Rickard, Claire M.
Central venous access devices (CVADs) are vital to enable treatment for children with cancer and other complex health conditions. However, complications effecting the CVAD wound are commonly reported. This study aimed to identify the incidence and prevalence of CVAD-associated skin complications current management, and characteristics associated with complication development, in pediatrics. A prospective observational study performed across medical, oncology, and hematology departments at a tertiary pediatric hospital in Australia, between April and July 2017. Children admitted with CVADs were assessed twice weekly for CVAD-associated skin complications and associated signs and symptoms. The data were analyzed using descriptive statistics (i.e., proportions, frequency) and time-to-event multivariable regression (i.e., hazard ratios [HRs]). Two hundred and seventy-one CVADs were reviewed over 43, 787 catheter days, with over one eighth of participants (14%; n = 37) having a CVAD-associated skin complication during their admission (0.95 per 1, 000 catheter days, 95% confidence interval [CI; 0.61, 1.17]), most commonly contact dermatitis (11%; n = 29; 0.72 per 1, 000 catheter days 95% CI [0.50, 1.04]). Within biweekly checks the median point prevalence of complications varied between 0.4% and 11% and clinical management was wide-ranging. A primary diagnosis of oncology (HR 2.89, 95% CI [1.10, 7.62]) or medical/surgical (HR 2.55, 95% CI [1.04, 6.22]) conditions; plain, nonbordered polyurethane dressings (HR 4.92, 95% CI [2.00, 12.13]); and poor dressing integrity (HR 2.64, 95% CI [1.18, 5.92]) were significantly associated with contact dermatitis. In conclusion, substantial numbers of pediatric patients experience CVAD-associated skin complications, and innovations are necessary to identify, prevent, and treat these health care–associated injuries.